Acute otitis media pneumococcal disease burden and nasopharyngeal colonization in children due to serotypes included and not included in current and new pneumococcal conjugate vaccines. (31st December 2023) - Pichichero, Michael; Malley, Richard; Kaur, Ravinder; Zagursky, Robert; Anderson, Porter
ABSTRACT: Introduction: Despite the introduction of effective pneumococcal conjugate vaccines (PCV), Streptococcus pneumoniae remains a major cause of acute otitis media (AOM) worldwide. New, higher valency vaccines that offer broader serotype coverage have been recently developed and others are in development. However, given the capsular serotypes expressed by pneumococci causing AOM, it is unclear to what extent differing or higher valency PCVs will provide additional protection. Areas Covered: We conducted a systematic literature search of the MEDLINE database to identify articles published from January 2016 to September 2021 in 4 low and middle income and 10 high-income countries. We searched PubMed with terms: ( Streptococcus pneumoniae ) OR pneumococcal AND serotype AND (conjugate vaccine). We evaluated serotype distribution and the actual or projected coverage of pneumococcal serotypes by PCV10 (GlaxoSmithKline), PCV13 (Pfizer), PCV10SII (Serum Institute of India) PCV15 (Merck) and PCV20 (Pfizer). Expert Opinion: Our review highlights the important epidemiological differences in serotype distribution and coverage by existing and higher valency vaccines to protect against AOM in children. These data provide support for further evaluation of serotype-independent vaccines for optimal control of pneumococcal AOM disease worldwide.